THE ROLE OF EFFICIENT MANAGEMENT OF ORGANIZATION IN THE DECREASE OF RECEIVABLES - Ковальчук, Вероніка; Мосьпан, Оксана; Стороженко, Альона (Socio-economic relations in the digital society, 2019)
The article investigates the theoretical aspects of management of accounts receivable in the system of settlements with buyers and customers, which will infl uence on the level of solvency of the enterprise and its financial status. Also, the article considers the main features and role of the management system of the organization in reducing the amount of receivables in the enterprise. Th e features of the management system of the organization are defined and the most frequently used methods of managing accounts receivable at the enterprises of Ukraine in the modern conditions are revealed. Th e need for management of receivables is determined for the non-admission of significant volumes of bad receivables, which, in turn, leads to deterioration of the financial state of the enterprise, deprives its investment attractiveness, and sometimes leads to bankruptcy. The concept of efficiency and effectiveness of the management system is considered. Two ways of controlling receivables are analyzed: independent management and outsourcing management and measures implemented by managers at each of the methods of management. The stages of the management of accounts receivable are considered. Also discussed are the strategies of credit policy, namely: conservative, moderate and aggressive, which are applied by enterprises depending on the level of profi tability and risk; analyzed the advantages and disadvantages of each. Th e necessity of restructurings of receivables, especially refi nancing, the main forms of which is factoring, forfeiting and accounting of bills, is indicated.
Keywords: accounts receivable; settlements with customers and customers; management systems; counteragents; commercial loans